2003
DOI: 10.1111/j.1749-6632.2003.tb07400.x
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella henselae and Borrelia burgdorferi Infections of the Central Nervous System

Abstract: To investigate the role of B. henselae in patients with symptoms suggesting neuroborreliosis, serum and cerebrospinal fluid samples were tested with serological and PCR methods. Among 17 examined patients, in 12 cases Borrelia burgdorferi infections were detected, in 1 case Bartonella henselae infection was ascertained, and in two patients mixed B. burgdorferi and B. henselae infections were found. These results indicate that mixed infections should be taken into consideration in establishing diagnosis of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 4 publications
(3 reference statements)
0
29
0
Order By: Relevance
“…For example, patients with ongoing symptoms attributed to chronic Lyme disease have been shown to be co-infected with Bartonella sp. [16,35] or Babesia sp. and Ehrlichia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with ongoing symptoms attributed to chronic Lyme disease have been shown to be co-infected with Bartonella sp. [16,35] or Babesia sp. and Ehrlichia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Babesia sp., the causative agents of babesiosis are transmitted by ixodid ticks and are capable of infecting a wide variety of vertebrate hosts including humans and cattle [20]. Co-infections of Borrelia burgdorferi sensu lato with Bartonella henselae have been found in patients presenting symptoms of atypical neuroborreliosis [16,35] while mice have been found to be naturally co-infected with Borrelia burgdorferi, Babesia microti and a novel Bartonella sp. in the USA [21].…”
Section: Introductionmentioning
confidence: 99%
“…(11,12,19,23,25,28,29). This suggestion was based on indirect data for detection of bacterial DNA in ticks (18,19,24), humans exposed to tick bites (30), or serologic evidence of co-infection of humans with pathogens known to be transmitted by ticks (11,36).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, several case studies have reported patients with concurrent Bartonella seropositivity and detection of Bartonella spp. DNA in their blood, along with B. burgdorferi infection of the central nervous system after tick bites (11,29). Moreover, Bartonella spp.…”
mentioning
confidence: 99%
“…There have been descriptions of the simultaneous presence of Borrelia and Chlamydia in the synovium of patients with Lyme arthritis (39). Also, concurrent infection of the central nervous system by B. burgdorferi and Bartonella henselae has been recently described, representing a novel tick-borne disease complex (40,41).…”
Section: Is Lyme Disease-like Syndrome a New Tick-borne Disease?mentioning
confidence: 99%